Commanders of the Great Victory - A. D. Borshchov (Vestnik MGIMO-Universiteta)
The honorary title of «commander» as well as the «admiral» is granted to a military or naval figure on the basis of public recognition of his personal contribution to the success of actions. Generals are usually individuals with creative thinking, the ability to foresee the development of military events. Generals usually have such personality traits as a strong will and determination, rich combat experience, credibility and high organizational skills. In an article dedicated to the 70th anniversary of the Soviet victory in the Great War examines the experience of formation and practice of the most talent-ed Soviet military leaders.